2015
DOI: 10.31661/gmj.v4i1.359
|View full text |Cite
|
Sign up to set email alerts
|

Stroke subtypes in southern Iran

Abstract: Objective: To investigate about frequency of different subtypes of stroke in south of IranMethods: This  is a retrospective, single-center study  conducted at Namazi Hospital, Shiraz, south of Iran. Age, sex, length of hospitalization and  mortality  of  stroke patients were recorded by reviewing hospital medical records.Results: 16 351 patients (53.6% male, 46.4%female) were recruited.  Ischemic stroke (10750 patients, 65.7%), intracerebral hemorrhage(3282 patients,20.1%) and subarachnoid hemorrhage(1057 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Meanwhile, epidemiological characteristics of stroke in Iranian population are different with other countries. Both population-based and hospital-based studies showed that incidence and mortality of stroke in Iran is higher than most western countries [1,2]. Higher rates of patients with young-adult stroke in Iranian population are a prominent feature too [3].…”
mentioning
confidence: 99%
“…Meanwhile, epidemiological characteristics of stroke in Iranian population are different with other countries. Both population-based and hospital-based studies showed that incidence and mortality of stroke in Iran is higher than most western countries [1,2]. Higher rates of patients with young-adult stroke in Iranian population are a prominent feature too [3].…”
mentioning
confidence: 99%